Structure Of Stigmasterols in Bran of Red Rice from Minahasa Regency, North Sulawesi, Indonesia - Emma Mauren Moko; Dino Rahardiyan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Rice bran contained important bioactive phytochemical components such as tocopherol, tocotrienol, and γ-oryzanol, and one of the components of γ-oryzanol is stigmasterol. The aim of the present study was to isolate and identify stigmasterol in native red rice bran extract. The isolation of sterol from red rice bran extract was performed by using Thin Layer Chromatography (TLC) and followed by identification by Fourier Transformed Infrared Spectroscopy (FTIR) and Nuclear Magnetic Resonance (NMR). The TLC single spot originated from crude red rice hexane extract was observed at 365 nm UV and the FTIR spectra analysis result showed that the OH group was indicated by 3436,9 cm-1 absorption. While absorption regions of 2931,6 to 2852,5 cm-1 indicate the presence of single bond CH. The data of 1H-, 13C- and 2D-NMR of rice bran sterol indicated that the single spot obtained in TLC analysis was stigmasterol. It can be concluded that native red rice variety of North Sulawesi contained stigmasterol and potential as a native antioxidant sources.